Manajemen Strategi dalam Meningkatkan Pendidikan Yang Kuat - Tsuraya, Febia Ghina; Sabina Tri Rizkiani; Hesti Kusumaningrum (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
This study analyses the application of strategic management in improving the quality of education. The method employed was a literature review, involving the collection of data from various sources including journals, books and articles. The findings indicate that effective strategic management encompasses various key elements such as creating a sense of urgency, the use of new curricula and programmes, the setting of ambitious goals, and a more selective student admission process. Furthermore, appropriate learning strategies and additional support for students experiencing difficulties have also been shown to improve academic achievement. Strategic management in education requires environmental analysis, strategy formulation, proper implementation, as well as continuous evaluation and control.